Posterior lower uterine segment caesarean hysterotomy, an innovative surgical technique to avoid classical hysterotomy: Case report and discussion - Kyungu M Kime; Lisa Bazzett-Matabele; Mercy N Nassali; G Justus Hofmeyr (SAGE Open Medical Case Reports)
A 40-year-old patient underwent laparotomy at term gestation for a 25-cm lower abdominal mass arising from the lateral wall of the uterus, with an extensive secondary blood supply from the lower uterus and bladder, preventing access to the anterior lower uterine segment. The gravid uterus was exteriorised over the patient’s thighs. A transverse posterior lower uterine segment hysterotomy was performed and a healthy 2920 g baby was delivered. A copper T 380A intrauterine device was placed at the fundus and the insertion tube passed through the cervix for retrieval after the surgery. A Foley catheter uterine tourniquet was applied to allow bloodless excision of the tumour. Histological examination confirmed a leiomyoma with extensive hyalinisation. The few prior reports of posterior lower uterine segment caesarean hysterotomy were mainly for uterine torsion or placenta accreta spectrum. It is useful to be aware of this simple though counter-intuitive approach when faced with technical difficulties.